The Warburg effect in hominis: isotope-resolved metabolism in ccRCC. Issue 12 (December 2018) - Crooks, Daniel; Linehan, W.
A recently published study has evaluated metabolism in human clear cell renal carcinomas (ccRCCs) using intraoperative [13 C]glucose infusion during surgical procedures. The findings demonstrate aerobic glycolysis and repression of the Krebs cycle, confirming the existence of the Warburg effect in ccRCC tumours in vivo.